Amniotic fluid embolism - Kiranpreet Kaur; Mamta Bhardwaj; Prashant Kumar; Suresh Singhal; Tarandeep Singh; Sarla Hooda (Wolters Kluwer Medknow Publications, 2016)
Amniotic fluid embolism (AFE) is one of the catastrophic complications of pregnancy in which amniotic fluid, fetal cells, hair, or other debris enters into the maternal pulmonary circulation, causing cardiovascular collapse. Etiology largely remains unknown, but may occur in healthy women during labour, during cesarean section, after abnormal vaginal delivery, or during the second trimester of pregnancy. It may also occur up to 48 hours post-delivery. It can also occur during abortion, after abdominal trauma, and during amnio-infusion. The pathophysiology of AFE is not completely understood. Possible historical cause is that any breach of the barrier between maternal blood and amniotic fluid forces the entry of amniotic fluid into the systemic circulation and results in a physical obstruction of the pulmonary circulation. The presenting signs and symptoms of AFE involve many organ systems. Clinical signs and symptoms are acute dyspnea, cough, hypotension, cyanosis, fetal bradycardia, encephalopathy, acute pulmonary hypertension, coagulopathy etc. Besides basic investigations lung scan, serum tryptase levels, serum levels of C3 and C4 complements, zinc coproporphyrin, serum sialyl Tn etc are helpful in establishing the diagnosis. Treatment is mainly supportive, but exchange transfusion, extracorporeal membrane oxygenation, and uterine artery embolization have been tried from time to time. The maternal prognosis after amniotic fluid embolism is very poor though infant survival rate is around 70%.